2018
DOI: 10.7554/elife.36234
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of in utero cannabinoid exposure on cortical function

Abstract: Cannabinoids can cross the placenta, thus may interfere with fetal endocannabinoid signaling during neurodevelopment, causing long-lasting deficits. Despite increasing reports of cannabis consumption during pregnancy, the protracted consequences of prenatal cannabinoid exposure (PCE) remain incompletely understood. Here, we report sex-specific differences in behavioral and neuronal deficits in the adult progeny of rat dams exposed to low doses of cannabinoids during gestation. In males, PCE reduced social inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
132
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(167 citation statements)
references
References 80 publications
(130 reference statements)
19
132
8
1
Order By: Relevance
“…Therefore, we surmise that the sex‐specific behavioural deficits we here observed at early life stages after prenatal WIN exposure could be similar to those obtained by administering THC during the prenatal period. In support of this hypothesis, we recently demonstrated that prenatal THC administration (from GD 5 to GD 20) induced similar sex‐specific synaptic deficits in the prefrontal cortex of adult rats, without any sign of toxicity and/or gross malformations in the rat offspring as WIN did (Bara et al, ). However, in a recent inhalation mouse study, a dose of ~0.5 mg·kg −1 ·day −1 THC smoke from GD 5.5 to GD 17.5 produced deficits in fetal growth and reduced birth weights in cannabis‐exposed male offspring suggesting that low‐dose exposure to THC via inhalation can compromise fetal development (Benevenuto et al, ).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Therefore, we surmise that the sex‐specific behavioural deficits we here observed at early life stages after prenatal WIN exposure could be similar to those obtained by administering THC during the prenatal period. In support of this hypothesis, we recently demonstrated that prenatal THC administration (from GD 5 to GD 20) induced similar sex‐specific synaptic deficits in the prefrontal cortex of adult rats, without any sign of toxicity and/or gross malformations in the rat offspring as WIN did (Bara et al, ). However, in a recent inhalation mouse study, a dose of ~0.5 mg·kg −1 ·day −1 THC smoke from GD 5.5 to GD 17.5 produced deficits in fetal growth and reduced birth weights in cannabis‐exposed male offspring suggesting that low‐dose exposure to THC via inhalation can compromise fetal development (Benevenuto et al, ).…”
Section: Discussionmentioning
confidence: 71%
“…Our previous works demonstrated the ability of mGlu 5 positive allosteric modulation to correct synaptic and behavioural deficits induced by prenatal WIN exposure at adulthood (Bara et al, ). Along this line, we found that systemic treatment with the positive allosteric modulator of mGlu 5 receptors CDPPB (1.5 mg, i.p.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations